Direct C2–H alkylation of indoles driven by the photochemical activity of halogen-bonded complexes - Mamone, Martina; Gentile, Giuseppe; Dosso, Jacopo; Prato, Maurizio; Filippini, Giacomo (Beilstein Journal of Organic Chemistry, 2023)
A light-driven metal-free protocol for the synthesis of sulfone-containing indoles under mild conditions is reported. Specifically, the process is driven by the photochemical activity of halogen-bonded complexes formed upon complexation of a sacrificial donor, namely 1,4-diazabicyclo[2.2.2]octane (DABCO), with α-iodosulfones. The reaction provides a variety of densely functionalized products in good yields (up to 96% yield). Mechanistic investigations are reported. These studies provide convincing evidences for the photochemical formation of reactive open-shell species.
Keywords: alkylation; EDA complex; halogens; indoles; photochemistry